Life satisfaction after stroke and the association with upper extremity disability, sociodemographics, and participation. Issue 8 (28th October 2021) - Ekstrand, Elisabeth; Brogårdh, Christina
Abstract: Introduction: Remaining disability after stroke can reduce a person's life satisfaction. Because previous studies of life satisfaction show inconsistent results, there is a need for more knowledge regarding perceived life satisfaction after stroke and associated factors. Objective: To assess perceived life satisfaction after stroke in relation to Swedish reference values; and the association with upper extremity disability, sociodemographics, and participation. Design: Cross‐sectional study. Setting: University hospital. Participants: Seventy‐five persons (72% male) with mild to moderate disability in a stable phase after stroke. Interventions: Not applicable. Main Outcome Measure: Life satisfaction was assessed with the Life Satisfaction Questionnaire (LiSat‐11), which includes one global item Life as a whole and 10 domain‐specific items. Global life satisfaction and explanatory factors were evaluated in two multivariate logistic regression models. Results: Fifty‐three percent of the participants were satisfied with Life as a whole . Highest satisfaction was found for Family life (78%) and Partner relationship (77%) and lowest satisfaction for Vocational situation (32%), Sexual life (25%), and Physical health (23%). Life as a whole and most domain‐specific items showed a significantly lower proportion of satisfied persons compared to Swedish reference values. In the first regression model with factors of upper extremity disability, manual ability was the strongest explanatory variable for Life as a whole ( p value = .032, Nagelkerke R Square 0.117). In the second regression model, participation, social, and working status were the final explanatory variables ( p value = .006, Nagelkerke R Square = 0.207). Conclusion: Our findings indicate that persons with mild to moderate disability after stroke perceive overall less satisfaction with Life as a whole and domain‐specific items than the general Swedish population. To increase a person's life satisfaction after stroke, rehabilitation interventions should target a variety of aspects including enhancing functioning of upper extremity, reducing participation restrictions, and providing support regarding social and vocational situation.